PENGARUH ZAKAT PRODUKTIF TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT MISKIN DI KABUPATEN SRAGEN - Hani'in, Umi (El-Hayah, 2018)
Abstract : This study aims to determine: 1) the effect of capital on improving the welfare of poor communities in Sragen Regency; 2) the influence of income on improving the welfare of the poor in Sragen Regency; 3) the impact of consumption on the improvement of the welfare of the poor in Sragen Regency; 4) health effects on improving the welfare of poor communities in Sragen Regency; 5) the influence of education on improving the welfare of the poor in Sragen Regency; and 6) the influence of capital, income, consumption, health, and education together on improving the welfare of poor communities in Sragen Regency.The research method used in this research is quantitative research method. This research was conducted in BAZNAS and LAZISMU Sragen regency. The population in this research is all the students in BAZNAS and LAZISMU Sragen regency. Sampling technique in this research use accidental sampling with sample as much as 90 mustahiq. Test the instrument using validity and reliability test. Methods of data analysis using multiple linear regression analysis, classical assumption test consisting of normality test, multicollinearity test, heteroskedastic test, F test, and t test.The results of this study indicate that: 1) capital affects the improvement of welfare. It is obtained from t count (9,113) more than t table (1,992) and probability 0.000 more or less 0,05; 2) income affects the improvement of welfare. It is obtained from t count (2,760) more than t table (1,992) and probability of 0,007 more or less 0,05; 3) consumption affects the improvement of welfare. It is obtained from the t count (2,241) more than t table (1,992) and the probability of 0,028 more or less 0,05; 4) health affects the improvement of welfare. This is obtained from the t count (4.338) more than t table (1.992) and the probability of 0.000 more or less 0.05; 5) education affects the improvement of welfare. It is obtained from the tcount (14,993) more than t table (1,992) and the probability of 0.000 more or less 0.05; 6) capital, income, consumption, health, and education affect the improvement of welfare. It is obtained from the value of F count of 162.645 more than F table = 2.37 and sig. 0,000 more or less 0,05.Keywords: capital, income, consumption, health, education, and welfare improvement.